Antioxidant Capacity from Ethyl Acetate Fraction of Kenikir (Cosmos Caudatus K) - Khrisna Pangeran; Tatang Irianti Irianti; Hari Purnomo (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Antioxidant is an activity that inhibits oxidation reactions due to exposure to free radicals, the search for antioxidant compounds continues to be developed from natural sources. The purpose is to identify new sources of safe and inexpensive agents through antioxidant capacity from ethyl acetate fraction on kenikir leaves was evaluated through enzymatic and non-enzymatic in vitro models. The research began with the method of separating compounds from ethanol extracts and ethyl acetate fractions, quantification of total phenolics and flavonoids, antioxidant capacity tests with DPPH, and tyrosinase enzyme. The results of the study produced isolate E which was observed in a single stain with Rf 0,80. The compound has a typical marker worth 1734.07 cm-1 with an indication of stretching vibration movement on C-O. It has a maximum wavelength of Â± 216 nm, with an abundance of 49.75% and a retention time of 27.20 minutes. TPC and TFC test results, the water fraction is the most dominant value with 0.430 mgGAE/g and 0.056 mQE/g. DPPH assay results, isolate E has an IC50 value of 162.03 ppm and a %inhibition of 12.73%. The tyrosinase inhibition test of L-DOPA substrate was resulting an IC50 value of 77.51 ppm compared to kojic acid of 16.48 ppm.